Clinical Outcomes Following Simple or Complex Stenting for Coronary Bifurcation Lesions: A Meta-Analysis - Qun Zhang; Hengshan Huan; Yu Han; Han Liu; Shukun Sun; Bailu Wang; Shujian Wei (Clinical Medicine Insights: Cardiology, 2022)
Background: Stent placement remains a challenge for coronary bifurcation lesions. While both simple and complex stenting strategies are available, it is unclear which one results in better clinical outcomes. This meta-analysis aims to explore the long-term prognosis following treatment with the 2 stenting strategies. Method: Randomized controlled trials found from searches of the PubMed, EMBASE, and Cochrane Central Register of Controlled Trials were included in this meta-analysis. The complex stent placement strategy was identified as the control group, and the simple stent placement strategy was identified as the experimental group. Data were synthesized with a random effects model. The quality of the randomized controlled trials was assessed by Jadad scale scores. The clinical endpoints at 6 months, 1 year, and 5 years were analyzed. Results: A total of 11 randomized controlled trials met the inclusion criteria. A total of 2494 patients were included in this meta-analysis. The odds ratio [OR] of the major adverse cardiac events (MACEs) at 6 months was 0.85 (95% confidence interval [CI] 0.53-1.35; P  = .49, I 2  = 0%). The OR of the MACEs at 1 year was 0.61 (95% CI 0.36-1.05; P  = .08, I 2  = 0%). The OR of the MACEs at 5 years was 0.69 (95% CI 0.51-0.92; P  = .01, I 2  = 0%). Compared with the complex strategy, the simple strategy was associated with a lower incidence of MACEs at 5 years. Conclusion: Compared to the complex stenting strategy, the simple stenting strategy can better reduce the occurrence of long-term MACEs for coronary bifurcation lesions.